PKM Rekayasa Pembuatan Kartu Undangan Digital Sebagai Media Usaha Mandiri - Nurcahyawati, Enny; Wijayanto, Catur Sunu; Nugraha, Renanda Adhi (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
The rapid advancement of information technology has significantly impacted various sectors, including theinvitation printing industry. With the increasing use of the internet in Indonesia, digital invitation businesseshave become an attractive opportunity, offering practicality and cost efficiency compared to traditional printedinvitations. This writing aims to explore the development of digital invitation cards as an independent business,focusing on appealing designs and effective marketing strategies through online platforms and social media.Through literature study methods and the implementation of community service programs, it was found thatdigital invitations have several advantages. These advantages include lower costs, easy access, and customizableinteractive features such as animations, videos, and direct links to important event information. The importanceof implementing communicative and interactive designs is key to attracting consumer attention. An attractivedesign not only serves as a visual appeal but also conveys information more clearly and effectively.Additionally, using social media as a marketing channel can enhance market reach, allowing for rapiddissemination of digital invitations to a wider audience. With the right approach, digital invitation businessescan meet the market's growing demand for digital solutions. Innovation in design and marketing will create newbusiness opportunities for individuals or groups looking to leverage information technology, making thisindustry increasingly relevant in today's digital era. Community involvement in this process can also strengthenlocal communities and enhance digital literacy among users.